Pulmonary embolism as presenting feature of membranous nephropathy induced nephrotic syndrome (Indian Journal of Case Reports, 2019)
Severe pulmonary embolism as first-time presentation of Nephrotic syndrome is rare but Nephrotic syndrome secondary to membranous nephropathy (MN) may impose a greater thrombotic risk for unclear reasons. Here, we report the case of a 36-year-old female patient presented with complaints of sudden onset of shortness of breath since 4-5 days and features of right-sided heart failure. There was no preceding history of any chronic disease or renal disease. She was diagnosed as having a bilateral severe pulmonary embolism. Extensive workup and renal biopsy were done which was suggestive of primary membranous nephropathy.